2018
DOI: 10.1016/j.heliyon.2018.e00581
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of NiO:V2O5 nanocomposite and its photocatalytic efficiency for methyl orange degradation

Abstract: Vanadium oxide has been largely exploited as a catalyst in many industrial applications. In this article, we show the synthesis of vanadium oxide (V2O5): Nickel Oxide (NiO) composite using sol-gel method at optimum conditions. The composite nanomaterials were used to remove methyl orange from waste water via harnessing the photocatalytic activity of it which showed an excellent efficiency of removal at 88%, and 93% after the exposure to the light, and light with heating respectively. This will pave the way int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The starting amount of MO in deionized water was 1 mg/mL and the nanomaterial loading was 2 mg/15 mL while the UV absorbance was recorded at different time intervals ranging between 0 and 20 minas presented in Figure 4 . Consistent with the published literature, 2 – 10 in the present work, the degradation calibration graphs were prepared by taking the λ max after 2, 5, 10, and 15 minas given in Figure 4 .
Figure 4 ( A ) UV Vis spectrum of MO/MoO 3 -NiO-PdO-Pd solution in the presences of solar light, ( B ) absorption spectrum of MO/MoO 3 -NiO-PdO-Pd in dark conditions, and ( C ) the degradation percentages of MO by MoO 3 -NiO-PdO-Pd nanomaterial.
…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…The starting amount of MO in deionized water was 1 mg/mL and the nanomaterial loading was 2 mg/15 mL while the UV absorbance was recorded at different time intervals ranging between 0 and 20 minas presented in Figure 4 . Consistent with the published literature, 2 – 10 in the present work, the degradation calibration graphs were prepared by taking the λ max after 2, 5, 10, and 15 minas given in Figure 4 .
Figure 4 ( A ) UV Vis spectrum of MO/MoO 3 -NiO-PdO-Pd solution in the presences of solar light, ( B ) absorption spectrum of MO/MoO 3 -NiO-PdO-Pd in dark conditions, and ( C ) the degradation percentages of MO by MoO 3 -NiO-PdO-Pd nanomaterial.
…”
Section: Resultsmentioning
confidence: 70%
“…The starting amount of MO in deionized water was 1 mg/mL and the nanomaterial loading was 2 mg/15 mL while the UV absorbance was recorded at different time intervals ranging between 0 and 20 minas presented in Figure 4. Consistent with the published literature, [2][3][4][5][6][7][8][9][10] in the present work, the degradation calibration graphs were prepared by taking the λ max after 2, 5, 10, and 15 minas given in Figure 4.…”
Section: Catalytic Activity Of Moo 3 -Nio-pdo-pd To Degrade Momentioning
confidence: 81%
See 2 more Smart Citations
“…Applications within the chemical synthesis field remain nevertheless rare even though variety of studies have been reported targeting new photocatalytic processes via synthesizing of composite or doped catalyst. Wide range of reaction types has been presented by different authors, which includes oxidations [1][2][3], reductions [4], isomerizations [5], additions [6], cyclizations [7] and so on. As a fact, conventional industries tactics in this area rarely meet the present day sustainability requirements, environmental safety and power performance essentially for a green processes [6].…”
Section: Introductionmentioning
confidence: 99%